Effects of vitamin K supplementation on vascular calcification in chronic kidney disease: A systematic review and meta-analysis of randomized controlled trials - Geng, Chanyu; Huang, Liming; Pu, Lei; Feng, Yunlin (Frontiers in Nutrition, 2023)
Background There is conflicting data on the effect of vitamin K supplementation against vascular calcification in chronic kidney disease (CKD). We aimed to summarize current evidence from randomized controlled trials (RCTs) to determine whether vitamin K supplementation in CKD could attenuate vascular calcification. Methods A systematic search was performed in MEDLINE, EMBASE, and Cochrane Central Library. RCTs assessing the effect of vitamin K supplementation on vascular calcification in CKD and reported measures relevant to vascular calcification were eligible for inclusion. Effect outcomes are changes of biochemical and imaging measures of vascular calcification, as well as vascular elasticity reflected by pulse wave velocity. Safety outcomes included any adverse event and death. The risk of bias was assessed according to Cochrane handbook guidelines. Mean differences or standardized mean differences with 95% confidence intervals of absolute and relative changes of each studied outcome between experimental and control groups were pooled using a random-effects model. Results In all, ten RCTs with 733 patients were included. Pooled results indicated a decrease in serum biomarkers relevant to vascular calcification to a certain extent, mild improvement in vascular elasticity reflected by PWV, yet, no significant change in calcification scores derived from radiology examinations. Half of the included studies had low risk of bias. Conclusions Therefore, there is not yet solid evidence to support protective effects of vitamin K supplementation against vascular calcification in CKD. The results of ongoing RCTs are needed to further elucidate the value of vitamin K in this field. The study was registered on PROSPERO (Identifier# CRD42022343857).